The Effect Of Training And Motivation On Improving Employee Performance Through Productivity As A Mediation Variable: A Conceptual Study Of Human Resource Development At Bank Jatim - Aldian Firdaus Permana (JURNAL MANAJEMEN MOTIVASI, 2026)
This study conceptually examines the impact of training and motivation on employee performance through productivity as a mediating variable in the context of human resource development at Bank Jatim. Using a literature-based conceptual approach, the study finds that training enhances skills, motivation fosters commitment, and productivity bridges their influence on performance. An optimal synergy among these elements significantly improves employee performance. The findings offer theoretical and practical implications for HR development strategies in banking institutions.